Analisis Putusan Pengadilan Negeri Padangsidimpuan Tentang Penjatuhan Hukuman Terhadap Pelaku Tindak Pidana Melarikan Anak (Studi Kasus Di Pengadilan Negeri Padangsidimpuan) - BUSYRO, Marwan (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2018)
ABSTRACTBased on the material used in this study, where the people involved in the research at the Padangsidimpuan State Law Court at this time can ask for a very difficult to do these actions, thus the authors make mistakes namely, what is the opinion The judge in the verdict has expressed respect for those who committed crimes against minors, how they were handed down to people who were related to these children.While the purpose of the research is to find out the judge in the decision has expressed respect for the people who committed crimes against children under the age of general and to the sums committed against the radius of criminal acts of underage boys in accordance with the Law . The research method used in this research is descriptive research which means that research is conducted with the results of interviews with respondents and also conducts research on the data or files related to this research and also by using practices issued by the court. Padangsidimpuan which has permanent legal force by conducting field research (Library Research) and Library Research (Field Research) and the techniques or tools that the writer uses in collecting data both in the field and in conducting interviews with respondents met by the author and data taken from documents The context used in this study is Interview (Interview), namely by asking questions directly to respondents who have previously determined it and the Documentation Study only with discussions that have been archived in Padangsidimpuan District Court which will then be analyzed by Induction and DeductionKeywords: Analysis, Court Decision, Child Escape